Association of Kawasaki disease with Staphylococcus aureus infection - Gautam, Piyush; Sharma, Nivedita; Singh, Parwinder (Indian Journal of Case Reports, 2018)
Kawasaki disease (KD) is a common medium vessel vasculitis in children of unknown etiology and is the most common cause of pediatric acquired heart disease. Diagnosis of KD is based on a set of clinical criteria, none of which is individually pathognomonic for this condition. Infections are being considered as one of the predisposing factors. Here, we present three cases, where Staphylococcus aureus bloodstream infection was found as the inciting trigger for Kawasaki disease.